PENGARUH LINGKUNGAN, PRODUK, HARGA DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK RAMAH LINGKUNGAN PADA KFC KOTA PALOPO - Dhea Fadillah; Fasiha Fasiha; Nurfadilah Nurfadilah (Program Studi Perbankan Syariah, IAIN Palopo, 2024)
The aim of this research is to analyze more deeply the extent to which environmental awareness (Green Awareness) influences purchasing decisions for environmentally friendly products among KFC consumers in Palopo City. Palopo City has a diverse group of consumers with different levels of environmental awareness, so it can be explored differences in consumer preferences and behavior. This research is categorized as associative quantitative research, where the research instrument is in the form of a questionnaire. The population in this research is KFC consumers in Palopo City. The sampling technique uses a purposive sampling method. The samples taken in this research were 100 samples. The measuring tool is proven to be valid and reliable for research instruments. Multiple regression analysis was used to test the research hypothesis. The results of this study show that: (1) there is a positive and insignificant influence of awareness of the environment on the decision to purchase environmentally friendly products, (2) there is a negative and insignificant influence of awareness of environmentally friendly products on the decision to purchase environmentally friendly products (3) there is positive and significant influence of price awareness on purchasing decisions for environmentally friendly products (4) there is a positive and significant influence of brand awareness on purchasing decisions for environmentally friendly products, (5) consumer concern for the environment, awareness of environmentally friendly products, price awareness and awareness Brands simultaneously have a significant influence on purchasing decisions for environmentally friendly products at KFC Palopo City.